Cesarean Section in a COVID-19 Positive Patient with Takayasu Arteritis: A Case Report - Lamsal, Ritesh; Bista, Navindra Raj; Acharya, Utsav; Joshi, Pankaj; Shrestha, Anil (Journal of BP Koirala Institute of Health Sciences, 2020)
Takayasu arteritis is an idiopathic, granulomatous aorto-arteritis that usually affcts young or middle-aged women. The anesthetic management of patients with Takayasu arteritis undergoing cesarean section with COVID-19 is challenging. Patients may have concomitant hypertension, tissue hypoperfusion with the potential for major perioperative cardiovascular complications. The challenges increase considerably in resource-limited settings. We report the case of a 27-year-old primigravida at 39 weeks of gestation with concomitant Takayasu arteritis, chronic hypertension, hypothyroidism, and COVID-19, who underwent an elective cesarean section at our hospital. She incidentally tested positive for SARS-CoV-2 after admission to the hospital. The cesarean section was successfully performed under subarachnoid block. We are not aware of any previous publication describing the anesthetic management in patients with Takayasu arteritis and COVID-19 undergoing cesarean section.